Comparison of cutting and coagulation properties of 1.56 and 1.94 µm fiber lasers and a 0.98 µm semiconductor laser - M. A. Ryabova; M. Yu. Ulupov; N. A. Shumilova; G. V. Portnov; E. K. Tikhomirova; M. E. Malkova (Бюллетень сибирской медицины, 2022)
Aim of the study was to compare the cutting and coagulation properties of 1.56 and 1.94 μm fiber lasers with those of a 0.98 μm semiconductor laser.Materials and methods. A comparative study of the biological effects of 1.56 and 1.94 µm lasers and a 0.98 µm semiconductor laser used in a constant, continuous mode was carried out. The cutting properties of the lasers were evaluated on the chicken muscle tissue samples by the width and depth of the ablation zone formed via a linear laser incision at a speed of 2 mm/s, while the coagulation properties were assessed by the width of the lateral coagulation zone. The zones were measured using a surgical microscope and a calibration slide. For statistical analysis, power values of 3, 5, 7, 9, and 11 W were chosen for each laser wavelength.Results. Analysis of the findings confirmed that laser wavelength had a statistically significant effect on the linear dependence between incision parameters and laser power. It was found that the 1.56 μm fiber laser (water absorption) had a greater coagulation ability but a comparable cutting ability compared with the 0.98 μm laser (hemoglobin absorption). When used in the power mode of 7W or higher, the 1.94 µm laser provided superior cutting performance compared with the 0.98 µm semiconductor laser at the same exposure power. Elevating the power in any of the lasers primarily increased the width of the ablation zone, and to a lesser extent – the crater depth and the width of the lateral coagulation zone. Therefore, in comparison with the 0.98 μm semiconductor laser, higher radiation power in the 1.56 and 1.94 μm lasers mainly influences their cutting properties, expanding the width and depth of the ablation zone, and has a smaller effect on their coagulation ability.Conclusion. The findings of the study showed that the 1.56 and 1.94 μm fiber lasers have better coagulation properties in comparison with the 0.98 μm semiconductor laser. was statistically proven that all incision characteristics (width of the lateral coagulation zone, depth and width of the ablation zone) for the 1.56, 1.94, and 0.98 μm lasers depend on the power of laser radiation. The 1.94 µm laser is superior to the 0.98 µm laser in its cutting properties.